The effect of the addition of SiCp on the mechanical behaviour of silane treated epoxy and polyester composites reinforced with unidirectional carbon fiber fabric. - Benham, A.; Kumar, K.K.Ajith; Pandian, M.Satha Siva; Golden Paul, C.Stanley (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
The prime material for performance intensive applications is carbon fiber reinforced polymer composites (CFRPC). Researchers have improved the properties of CFRPC by creating a stronger interface between the constituents either by treating the fiber surface with alkalis, oxidization agents or gases. However, there is a possibility of fiber damage during treatment. In this investigation two different matrices viz., epoxy and polyester were modified by incorporating (3-Aminopropyl)trimethoxysilane coupling agent and silicon carbide particulate filler (SiCp). The effect of matrix modification on the mechanical behaviour of CFRPC is investigated in terms of tensile, flexural and impact properties. It was observed that CFRPC with modified matrices had better properties due to improved adhesion between the constituents. In particular, carbon fiber reinforced 10 wt. % SiCp filled silane treated polyester matrix composite had better mechanical properties. The results have been supplemented with morphological investigation.